PENERAPAN SANKSI PIDANA TERHADAP PENGEMUDI ANGKUTAN UMUM TIDAK MEMILIKI SERTIFIKAT PENGEMUDI ANGKUTAN UMUM BERDASARKANPERATURAN DAERAH KOTA PEKANBARU NOMOR 2 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Royani, Anik Novia; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Traffic problems are one problem that is difficult to solve. The number of traffic violations is still quite high, one of which is the violation of public transport drivers who do not have public transport driver certificates. Whereas in Pekanbaru City Regulation Number 2 of 2009 concerning Road Traffic and Transportation it is said that in Article 72 drivers of public transport must have a driver certificate of public transport to reduce the number of traffic accidents caused by lack of expertise in driving. The problem in this writing is how the application of criminal sanctions against drivers of public transport does not have a public transport driver certificate based on the Regional Regulation of Pekanbaru City Number 2 of 2009 concerning Road Traffic and Transportation.The purpose of this study was to find out the application of criminal sanctions against public transport drivers who committed violations and to find out the factors for violations committed by drivers of public transport did not have public transport driver certificates, the research method used in this draft was sociological legal research. Legal research is carried out by means of interviews by giving questions to informants related to the title taken.Factors and the application of sanctions against traffic violations committed by public transport drivers in the legal area of the Pekanbaru City Police Resort include weak legal awareness, and a weak supervision system, while the application of criminal sanctions is not implemented properly, arguing that there are still small fines in The article is only subject to imprisonment, not imprisonment, whereas in Articles 72 and 73 of the Regional Regulation of Pekanbaru City Number 2 of 2009 concerning Road Traffic and Transportation, public transport drivers who do not have a public transport driver certificate will be subject to three months imprisonment or a fine of Fifty million Rupiah.Keyword : The Application Of Criminal Sanction –Public Transpot Driver – Does Not Have a Driver Certificate – Traffic And Road Transport